Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/02614360500504693
|View full text |Cite
|
Sign up to set email alerts
|

Grandfatherhood and Leisure

Abstract: This paper explores the meanings and values attached to grandfatherhood for a range of older men who have recently retired from paid employment. It focuses on the spaces of grandfatherhood and the meanings they attach to time spent with grandchildren. The empirical study involved 12 semi-structured interviews with grandfathers from diverse ethnic backgrounds. The data are examined from a theoretical position that recognises the significance of unequal gender relations within families in determining choice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
1
19
2
4
Order By: Relevance
“…This reproduces a persistent gendered division of labour in grandparenthood, continually gendering the spaces in which caring is enacted across the lifecourse. In contrast to findings by Scraton and Holland (2006) however, these men are not using these spaces because they see care for grandchildren as work and therefore detrimental to their ability to seek leisure. They are incorporating their grandchildren in these spaces, constructing distinctly masculine practices of care later in life in response to the needs of their grandchildren, as well as their ageing highlighting the relational nature of identity performances.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This reproduces a persistent gendered division of labour in grandparenthood, continually gendering the spaces in which caring is enacted across the lifecourse. In contrast to findings by Scraton and Holland (2006) however, these men are not using these spaces because they see care for grandchildren as work and therefore detrimental to their ability to seek leisure. They are incorporating their grandchildren in these spaces, constructing distinctly masculine practices of care later in life in response to the needs of their grandchildren, as well as their ageing highlighting the relational nature of identity performances.…”
Section: Discussioncontrasting
confidence: 49%
“…This is spatially contingent and the men draw on spatial metaphors and gendered divisions of labour established earlier in the lifecourse to justify and make sense of their practices as grandfathers. While Scraton and Holland (2006) based their argument on a limited sample they also found that the established division of labour between leisure and childcare from fatherhood often continues into old age because men are reluctant or unable to break these patterns. This suggests that the occupation of particular spaces is significant to the performances of intergenerational interaction, and consequently how men perform their identities and caring obligations as old men, reproducing these gendered carescapes later in the lifecourse.…”
Section: My Wife More As the Provider Of Food And Home Comforts Imentioning
confidence: 99%
“…Scraton a Holland [2006] upozorňujú, že starí otcovia z ich výskumnej vzorky sú si vedomí generačnej obmeny a toho, že zmenené sociokultúrne prostredie a tiež vnúčatá ako jeho súčasť od nich očakávajú výraznejšie zapojenie, expresívnosť a výchovu. Ako špeciálne dôležité sa preto ukazuje zohľadňovanie veľkej kohorty mladších starých otcov v treťom veku [Laslett 1991], ktorých vzťa-hy s vnúčatami môžu byť v porovnaní so starootcovskými vzťahmi predchádzajú-cich generácií redefinované.…”
Section: Vykročenie K Aktívnejšiemu Napĺňaniu Roly Starého Otca?unclassified
“…Prezentovaný text rozširuje skôr neveľké rady empirických štúdií a pokúšame sa v ňom o revíziu zásadné-ho teoretického modelu starootcovstva, ktorý navrhujú a rozpracovávajú Bates a Taylor [2013]. Vychádzame pritom z existujúcich empirických štúdií [Cunningham-Burley 1984;Kivett 1985;Waldrop 1999;Roberto, Allen, Bleiszner 2001;Scraton, Holland 2006;Mann, Khan, Leeson 2009] a z transgeneračnej perspektívy priestorov a podôb starostlivosti Tarrant [2010Tarrant [ , 2012Tarrant [ , 2013.…”
Section: Zhrnutie a Diskusiaunclassified
“…Feminist researchers have long argued that it is women who predominantly take on care responsibilities for children (Brannen andNilsen 2006, McKie, Gregory andBowlby 2002) and grandchildren (Scraton and Holland 2006), and that this is spatially reproduced in an ongoing division of labor that constructs men as breadwinners or pursuers of outdoor leisure pursuits, and women as carers and associated with the domestic. This is supported to some extent, by the grandfathers who took part in this study (Tarrant 2013).…”
Section: Old Age: Grandfathering and Caring For Grandchildrenmentioning
confidence: 99%